Ulama dan Peranan Dakwah di Pesisir: Kontribusi dan Dampaknya - Kholiq, Abd (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2024)
Islamic preaching should not stop in the preaching implementation system. So what needs to be prepared in the relay of preaching implementation is the establishment of Islamic educational institutions in the form of Islamic boarding schools as the forerunner of Islamic educational institutions. This study focuses on the role of ulama in preaching in coastal areas, exploring their contributions in social, cultural, and religious aspects. Through in-depth analysis, this article identifies the preaching strategies used by ulama and the significant impacts they bring to coastal communities. Ulama as a central force in the spread of religion, so here this study is conducted within the framework of seeing the extent of their role and contribution in the implementation of their preaching, so that the impact made in the spread of Islam will be known.